Estudo da quiropterofauna (Chiroptera; Mammalia) em área nativa e de Sistema Agroflorestal (SAF) em Pirassununga, São Paulo, Brasil - Silva, Ana Elisa Teixeira da (Universidade Federal de São Carlos, 2017)
The intense fragmentation of natural areas, like Semideciduous Forest (Native Area), with consequent pressure under native fauna, emphasizes the search for alternatives to the monoculture system, like Agroforestry Systems (AFSs), which simultaneously cultivate agricultural and native species and can contribute to the subsistence and conservation of species. The present study aimed to investigate which species of bats occur in the Native and AFS areas of CEPTA-ICMBio, Pirassununga (SP). It was recorded 228 individuals belonging to 20 species and three families. About species, 14 (N = 95) were captured in Native Area and 13 (N = 133) in AFS. The results point to a certain degree of species similarity among the studied areas, absence of significant differences on diversity index and similar richness coefficients among Native and AFS areas. Although the AFS can function as corridor between matrices and can contribute to the maintenance of common frugivorous, nectarivorous and insectivorous bats species, probably due the presence of spontaneous pioneer plants in studied areas, it is suggested the greater plant and structural diversity of Semideciduous Forest fragment can ensure the persistence of bat species considered uncommon. About the diet and dispersal seeds, the great majority of fecal samples (N=83 out of N=87) was obtained from phyllostomid bats and contained 16 food items: fruits of Solanaceae, Piperaceae, Urticaceae, Moraceae, Siparunaceae and exotic Muntingia calabura, nectar of Mabea sp., arthropods remains (insects and spider) and clay. While the other four fecal samples were obtained from vespertilionid bats and contained insects remains.
Study of chiropterofauna (Chiroptera; Mammalia) in native and agroforestry system area (AFS) in Pirassununga, São Paulo, Brasil
Keywords: Morcegos; Floresta estacional semidecidual (Área nativa); Sistema Agroflorestal (SAF); Riqueza, diversidade e similaridade; Dieta e sementes dispersadas; Bats; Agroforestry system (AFS); Richness, diversity and similarity; Diet and dispersal seeds; Semideciduous Forest (Native Area); CIENCIAS BIOLOGICAS::ECOLOGIA; OUTROS